Chenier Morphodynamics on the Amazon-Influenced Coast of Suriname, South America: Implications for Beach Ecosystem Services - Anthony, Edward J.; Brunier, Guillaume; Gardel, Antoine; Hiwat, Michael (Frontiers in Earth Science, 2019)
The 350-km long coast of Suriname, South America, is part of a unique system in the world characterized by large-scale mud supply from the Amazon and exposed to Atlantic waves. Large banks migrate alongshore from the Amazon to the Orinoco delta, separated by ‘inter-bank’ zones. Banks dissipate waves, and create new land, aided by mangroves, whereas waves in inter-bank areas cause shoreline erosion, mitigated where sandy/shelly cheniers develop. Cheniers are rare due to sand/shell burial by mud. They assure coastal protection, and recreational and ecological services, notably providing nesting sites for marine turtles. Cheniers close to urban centres are under pressure from sand mining. In order to gain a better understanding of how cheniers develop and evolve, a study was conducted on Braamspunt beach, a turtle-nesting chenier in Suriname constructed from sand supplied by the Maroni River. Satellite images between 1987 and 2018 show that Braamspunt beach has progressively shortened, mainly through isolation of the beach by a mud bank migrating alongshore. Downdrift of the mud bank, the beach has migrated landward by wave overwash. Active commercial sand mining has further affected the beach. Partial sand sequestering at a multi-decadal timescale by migrating mud banks results in temporally fragmented and alongshore-variable sand transport. Field surveys (high-resolution topometry, drone photogrammetry, and wave measurements) conducted in February, 2016, enabled differentiation between a reworked sector (immediately downdrift of the mud bank), and a ‘sink’ sector adjacent to the Suriname River estuary. Sand sequestering at the bank’s leading edge and landward chenier migration deprive the downdrift beach of sand, generating beach scarping and lowering downdrift to balance an under-saturated longshore transport. Over only 3-4 days, the beach lost over 4200 m3 as a result of mud blanketing and overwashing. The subsisting beach is currently preserved from mud in its downdrift sector by mud liquefaction at the mouth of the Suriname River. This preservation is a morphodynamic adjustment between beach and the river jet, and without which Braamspunt beach would cease to exist. This effect assures beach availability for turtle nesting. The continued existence of Braamspunt beach is, however, endangered by sand mining.